2021
DOI: 10.1016/j.chest.2021.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Mental Health Disorders in Critical Care Physicians Facing the Second COVID-19 Wave

Abstract: BACKGROUND: Working in the ICU during the first COVID-19 wave was associated with high levels of mental health disorders.RESEARCH QUESTION: What are the mental health symptoms in health-care providers (HCPs) facing the second wave? STUDY DESIGN AND METHODS: A cross-sectional study (October 30-December 1, 2020) was conducted in 16 ICUs during the second wave in France. HCPs completed the Hospital Anxiety and Depression Scale, the Impact of Event Scale-Revised (for post-traumatic stress disorder), and the Maslac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(113 citation statements)
references
References 29 publications
3
73
0
6
Order By: Relevance
“…Similar findings were reported by Belanti et al, 2020, who found that workload and lack of emotional support at the workplace were particularly predictive of mental distress in terms of burnout among nurses during the pandemic [ 38 ]. A study on French HCWs in intensive care identified the fear of infecting themselves or relatives with the virus as a predictor of various mental health problems [ 39 ]. Additionally, in their systematic review, Skolaridis et al postulate that the fear of infecting relatives is an important stress factor for healthcare workers in epidemics and pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported by Belanti et al, 2020, who found that workload and lack of emotional support at the workplace were particularly predictive of mental distress in terms of burnout among nurses during the pandemic [ 38 ]. A study on French HCWs in intensive care identified the fear of infecting themselves or relatives with the virus as a predictor of various mental health problems [ 39 ]. Additionally, in their systematic review, Skolaridis et al postulate that the fear of infecting relatives is an important stress factor for healthcare workers in epidemics and pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…For example, for staff having worked 20 years at an elective orthopaedic outpatient clinic, qualifications to care for acute seriously ill COVID‐19 patients may be sparse. Therefore, considering competencies as suggested may not only decrease nurses’ distress (Azoulay et al., 2021 ; Heesakkers et al., 2021 ) but may also improve patient safety (Aiken et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sheer numbers of patients, as well as the time needed to put on and remove personal protective equipment, meant that the time available for each patient was inevitably less than normal, and many staff members felt they were unable to provide the quality of care that they would under non-pandemic conditions. Lack of effective treatments, difficulties communicating with patients and their relatives, the need to make rapid, complex ethical decisions regarding which patients to admit or when to withhold or withdraw treatment, responsibility for new, non-ICU-trained members of the team transferred from other units, and fears about catching the virus and passing it on to their own family members, all added to the psychological burden on ICU teams with high rates of insomnia, depression, anxiety, post-traumatic stress disorder, and burnout [ 38 , 39 , 40 , 41 , 42 , 43 ]. Various strategies have been proposed to try and limit some of the psychological impact, including adequate training and senior support for new or re-allocated staff, availability of clinical psychologists for individual assessments and consultation, and regular team debriefing and support sessions [ 44 , 45 ].…”
Section: Psychological Impact On Healthcare Workersmentioning
confidence: 99%